2013
DOI: 10.1037/a0031881
|View full text |Cite
|
Sign up to set email alerts
|

Hazardous drinking and family functioning in National Guard veterans and spouses postdeployment.

Abstract: The current study examined rates of alcohol misuse among National Guard (NG) service members and their spouses/partners, concordance of drinking behaviors among couples, and the effects of alcohol misuse, depression, and posttraumatic stress disorder (PTSD) on three measures of family functioning. This study is important because it addresses the topics of heavy drinking and family functioning in an at-risk population-NG service members returning from a combat zone deployment. We surveyed NG service members (1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
81
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(87 citation statements)
references
References 49 publications
(81 reference statements)
2
81
3
Order By: Relevance
“…In a study of National Guard couples 45-90 days post-deployment from OEF/ OIF/OND, recent combat exposure was not related to family outcomes (Blow et al 2013). Hazardous drinking, however, was associated with more marital/relationship distress and both service member and spouse depression were associated with lower relationship satisfaction, higher parenting stress, and more family chaos.…”
Section: Current Eramentioning
confidence: 99%
“…In a study of National Guard couples 45-90 days post-deployment from OEF/ OIF/OND, recent combat exposure was not related to family outcomes (Blow et al 2013). Hazardous drinking, however, was associated with more marital/relationship distress and both service member and spouse depression were associated with lower relationship satisfaction, higher parenting stress, and more family chaos.…”
Section: Current Eramentioning
confidence: 99%
“…The positive correlation between the alcohol use of couple members found in the general population was also found among currently serving and veteran military couples,25 26 31 although of a small to moderate effect size (r=0.27–0.48) 33. Only one study examined drinking concordance among current military couples 25. Blow et al reported that AUDIT scores were much higher in Service personnel than military spouses/partners (with an average difference of 7.4); however, both spouses or partners and personnel met AUDIT criteria for alcohol misuse in only 5.4% of couples 25.…”
Section: Resultsmentioning
confidence: 92%
“…However, this may differ depending on when during the deployment cycle surveys are conducted. As previously discussed, the highest AUDIT estimate of 10.7% from Blow et al 25 was obtained from a survey conducted in the 3 months following the return of Service personnel from deployment when couples may be celebrating their safe return. The length of deployment or separation from personnel also may play a role, with longer deployments of Service personnel significantly associated with negative spouse/partner drinking behaviours; over a 3-year period, 3.1 (95% CI 1.6 to 4.5) excess diagnoses of alcohol misuse per 1000 women were reported among spouses/partners of Service personnel deployed for longer than 11 months, significantly higher than the spouses/partners of personnel who did not deploy 32.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations